Metal-Organic framework-based Wood Aerogel for Effective Removal of Micro/Nano plastics - You, Dongyu; Zhao, Yujuan; Yang, Weiting; Pan, Qinhe; Li, Jiyang (Chemical research in Chinese universities, 2022)
T he large amount of microplastic pollution in the aquatic environment has been regarded as a major challenge facing the world. Although some traditional water treatment processes can effectively remove microplastics in the millimeter range, research is still needed to solve the problem of removing smaller microplastics. Here, we made a durable zinc metal-organic framework-based composite material ZIF-8@Aerogel by in situ growing ZIF-8 on wood aerogel fibers, which can successfully remove microplastics in simulated water and seawater. The removal efficiencies on micro/nano plastics including poly(1,1-difluoroethylene)(60–110 nm) and polystyrene(90–140 nm) reached 91.4% and 85.8%, respectively. This work is expected to provide a new and efficient way to remove small-sized microplastic particles in the environment.